Identifikasi Jenis Mineral Industri Dengan Xrd Pada Sampel Batupasir Formasi Ekmai, Distrik Ertsberg, Kabupaten Mimika, Provinsi Papua Tengah - Endang Hartiningsih (Fakultas Teknik Universitas Cenderawasih, 2023)
The sandstones of the Ekmai Formation are composed of various minerals, both metal and non-metallic minerals, especially industrial minerals. This study aims to identify the types of industrial minerals within the sandstones using XRD analysis. The main mineral identified is quartz. Other minerals groups are carbonates, clay, garnet, feldspar, amphibole, chlorite, epidote, and olivine.